The Origins of a Paper Money Economy - the Case of Norway - Lars Fredrik Øksendal (Norges Bank, 2009)
This article sketches the origins of paper money in Norway back to the last half of the 18th century and asks why there was no circulation of full-bodied coins even after notes had become convertible into silver at par in 1842. The argument put forward is that the choice of fiat paper money reflected the relative economic backwardness of the country. Although Gresham's law also applied for Norway, the most important reason paper money caught on and maintained that position as the most important part of the money stock was the chronic shortage of means of payment. In such a situation, bad money was not that bad after all. Moreover, times of war and political havoc besides, paper money managed to stay fairly stable and fulfil an essential function as a store of wealth. With time, paper money became institutionalised in the Norwegian economy, overwhelmingly dominating the domestic circulation and functioning as the key monetary reference (unit of account). Thus, convertibility in 1842 linked the domestic currency with international money at fixed rates, but had hardly any bearing on the domestic function of money.
hdl:11250/2497615
Keywords: E42; E58; N23; 330; Gresham's law; banknotes; bullion standard; convertibility; paper money